Optical Detection of the X-Ray Flash in the Very Fast Nova V1674 Her: Optical Contribution of the Irradiated Accretion Disk - Izumi Hachisu; Mariko Kato (The Astrophysical Journal)
V1674 Her is one of the fastest and brightest novae, characterized by dense optical photometry in the premaximum phase—a rise from g = 17 to 7 mag, over one-quarter of a day. We present a composite theoretical V light-curve model of its early rising phase, starting from a quiescent brightness of g = 19.2 mag. Our light-curve model consists of a hot and bright white dwarf (WD) and an irradiated accretion disk and companion star. We find that the earliest optical detection of an All Sky Automated Survey for Supernovae g -band brightness of g = 17.0 at t = 0.014 days from the onset of thermonuclear runaway can be explained with the irradiated accretion disk and companion star in the X-ray-flash phase of a 1.35 M _⊙ WD. This is the first detection in the optical of an X-ray-flash phase of a nova. Optically thick winds emerge from the WD photosphere at t = 0.04 days, and the optical flux is dominated by free–free emission from optically thin ejecta just outside the WD photosphere. Our free–free emission model V light curve reasonably reproduces the dense g light curve of Evryscope that spans from g = 14.8 (at 0.078 days) to g = 7.1 (at 0.279 days), including a sudden change of slope in the g light curve from a slow to a rapid rise at g = 14.3 on day 0.1. There is no indication of shocking power during the rising phase from g = 14.8 to 7.1.